A Series of Frequency Shift Antennas Based on Shape Blending. (3rd May 2021) - Wu, Aiting; Sun, Yuebin; Zhang, Pengquan; Du, Tiejun
Abstract : In this paper, an automatic antenna design method based on the shape blending algorithm is proposed. The algorithm is used to construct the shape of the wide slot of a CPW-fed antenna. Firstly, two basic shapes are chosen as the initial shape and the target shape. The shape blending process is then applied on them to get a series of shapes, which are used as the geometry structure of the wide slot. In this way, a series of CPW-fed wide slot antennas are obtained. And they have similar but gradually changing characteristics. The bandwidth ranges are 8.00–9.24 GHz, 7.95–9.05 GHz, 7.05–8.55 GHz, 6.95–8.13 GHz, and 6.55–7.50 GHz, respectively. The overall size of the antenna is 26 mm ∗  20 mm ∗  0.6 mm. Experimental results show that the resonant frequencies vary (via translation) with the change of slot shape in a specific frequency band. The experiments also validate that the antennas have omnidirectional radiation characteristics. The radiation gains and aperture efficiencies of the antennas are about 3.8–5.5 dBi and 57.7–83.0% at their centre frequencies, respectively. The experiment results show that the proposed antennas could be used in C-band and X-band radar applications.